Fibre function and perception during cutaneous nerve block. Issue 9 (September 1975) - Mackenzie, R A; Burke, D; Skuse, N F; Lethlean, A K
Abstract : In awake human subjects, neural responses in radial nerves to electrical stimulation were recorded with intrafascicular tungsten microelectrodes. Changes in the activity of individual fibre groups during blocking procedures were recorded and correlated with simultaneous alterations in the perception of standardized stimuli. Light touch sensibility in hairy skin appeared to depend on the integrity of A-beta-gamma fibres, cold and pinprick on A-delta fibres, and warmth and dull pain on C fibres.